THE PHENOMENON OF EDUCATIONAL RESONANCE IN THE CONTEXT OF DISTANCE LEARNING: INTERDISCIPLINARY APPROACH - Voznyuk, Oleksandr; Dubasenyuk, Oleksandra (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article outlines some aspects of the phenomenon of educational resonance in the context of distance learning. It is argued that the educational process becomes fundamentally resonant when pedagogical resonance takes place both in the context of communication mediated by distance learning technologies and direct communication of subjects of education in the academic environment, which is implemented at the level of verbal, extraverbal interaction, and interacts at the level of brain’s neurons of the communicants. The phenomenon of mirror neurons is considered, which should be understood as a cornerstone in the field of psychological and pedagogical sciences. It is noted that the pedagogical action of a teacher can be transmitted to participants in the educational process in the mode of mirror resonance at the level of the neural organization of their brain, when in the specified context the teacher discovers a new and rather important aspect in the set of his/her professional competencies.